Lung Function before and Two Days after Open-Heart Surgery - Charlotte Urell; Elisabeth Westerdahl; Hans Hedenström; Christer Janson; Margareta Emtner (Critical Care Research and Practice)
Reduced lung volumes and atelectasis are common after open-heart surgery, and pronounced restrictive lung volume impairment has been found. The aim of this study was to investigate factors influencing lung volumes on the second postoperative day. Open-heart surgery patients (n=107, 68 yrs, 80% male) performed spirometry both before surgery and on the second postoperative day. The factors influencing postoperative lung volumes and decrease in lung volumes were investigated with univariate and multivariate analyses. Associations between pain (measured by numeric rating scale) and decrease in postoperative lung volumes were calculated with Spearman rank correlation test. Lung volumes decreased by 50% and were less than 40% of the predictive values postoperatively. Patients with BMI >25 had lower postoperative inspiratory capacity (IC) (33±14% pred.) than normal-weight patients (39±15% pred.), (P=0.04). More pain during mobilisation was associated with higher decreases in postoperative lung volumes (VC: r=0.33, P=0.001; FEV1: r=0.35, P≤0.0001; IC: r=0.25, P=0.01). Patients with high BMI are a risk group for decreased postoperative lung volumes and should therefore receive extra attention during postoperative care. As pain is related to a larger decrease in postoperative lung volumes, optimal pain relief for the patients should be identified.